(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
In this study, an analysis of the problem of bullying in secondary schools has been carried out. To do so, comparison, generalization, observation, systemic analysis, theoretical cognition, and analogy methods are utilized. The necessity of pedagogical reacting to the stated problem has been proved. The authors present guidelines for countering the problem of bullying. The importance of humanization of relationships at school, beginning with leadership styles, goal-oriented formation of optimistic positions, and positive thinking of schoolchildren and teachers are emphasized. Particular attention is paid while working with the problem of bullying to the method of reliance on the strengths of an individual and the formation of its leadership qualities. The main components of socially significant knowledge: socio-psychological, socio-legal, and social-integrative, have been outlined. The formation of this knowledge will allow a person to avoid bullying or respond to it at the right moment. The need for a timely diagnosis of bullying has been accentuated.